Classification technology of machine-plucking high quality tea - ZHANG Lan-lan; DONG Ji-fen; TANG Meng; CAI Wei-zhi; WEN Zheng-jun; LUO Yao-ping (浙江大学学报. 农业与生命科学版)
Although the harvesting of fresh, high quality tea leaves has traditionally relied on hand-plucking, labor shortages and the rise in the cost of hand-plucking have restricted the growth of quality tea production and the development of the tea industry. This problem would be effectively resolved if the fresh tea leaves harvested through machine-plucking could be used for the production of high quality tea. However, few studies to date have been reported in this respect.Based on current machine-plucking technology, fresh tea leaves are difficult to harvest, as the raw material, consisting of mixed shoots and leaves, varies in size and tenderness. In order to meet the production standards of high quality tea, machine-plucking technology must be improved. This study aims to explore the technological development of the machine-plucking classification method of fresh tea leaves.Three methods of classification of fresh, machine-plucked tea leaves were compared in this study: 1) roll screen (6CXF-70 bulk tea leaves classification machine, MCF self-made high quality tea leaves classification machine); 2) flat circular screen (Zhechajing 766); and, 3) wind election (FX450 type). The raw material was classified by size and mass in varying sieve and wind condition. In addition, the mechanical compositions of classified fresh tea leaves were also analyzed to compare the classification effects.Among the fresh, machine-plucked tea leaves, which were not suitable for the manufacture of high quality tea, the 23.54% were standard shoots, 43.33% were coarse old shoots and 33.13% were other debris. The results of the roll screen method showed that the proportion of standard shoots classified by MCF was 19% higher than those classified by 6CXF-70 within the same classification range. The flat circular screen was unable to adequately separate shoots by size. The wind election method was more effective at removing debris, but it was not able to separate fresh, standard shoots from old, coarse shoots. The classification effect was vastly improved by combining the MCF and wind election methods. When the fresh, machine-plucked tea leaves were first classified by MCF and then by wind election, the proportion of standard shoots to coarse shoots rose by 16%, and the debris decreased by 23%. This result indicates that the MCF in combination with the wind election method is effective in separating standard shoots from debris. The classification effect, however, was not observed if the order of methodology was reversed. These results clearly indicate that adjusting the structure of classification mechanisms can result in greater separation of standard shoots to a certain extent.Although the three classification methods of roll screen, flat circular screen, and wind election all have the ability to separate fresh tea leaves by size, each method varies in effect. In conclusion, the roll screen method of classification results in more precise and standardized shoots, and the classification effect is most pronounced by combining the methods of MCF and wind election.